Perilaku Pemberian ASI Eksklusif pada Ibu Bekerja - Sari, Aprilia Nurtika (STIKES Telogorejo Semarang, 2023)
Breastfeeding is a natural process, babies have the right to receive exclusive breast milk which is continued until the age of two years. Working mothers face challenges in balancing breastfeeding and work, thereby increasing the risk of premature cessation of breastfeeding in general and exclusive breastfeeding in particular. The purpose of this study is to identify the exclusive breastfeeding behavior of working mothers at Posyandu Bonto, Desa Sumberkepuh Village, Kecamatan Tanjunganom, Kabupaten Nganjuk. The design of this research is descriptive with a cross sectional approach. The population in this study were all breastfeeding mothers who worked at Posyandu Bonto, Desa Sumberkepuh Village, Kecamatan Tanjunganom, Kabupaten Nganjuk, with a total of 25 respondents. The sample was taken using a total sampling technique. The research results showed that the majority of respondents were aged 20-35 years (88%), had a high school education/equivalent (40%), worked as laborers and private employees (44% each), had working hours > 8 hours (52%), and distance between residence and place of work < 10 km (60%). All respondents had received information about exclusive breastfeeding (100%). Most sources of this information were health workers (60%). Most respondents provided exclusive breastfeeding for their babies, namely 14 respondents (56%). Therefore, in many cases, partners, family, friends and health workers must play their role in supporting working mothers to successfully provide exclusive breastfeeding for their babies.